Pengaruh Brand Ambassador Terhadap Brand Image Shampoo Sunsilk - Annisa Leovani; Anisti; Tuty Mutiah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
In an effort to strengthen its brand image amid the competitive hair care industry, Sunsilk launched the #MyKilauTime campaign by appointing tiara andini as its brand ambassador. As a public figure widely recognized by the younger generation, her presence is considered capable of creating an emotional connection between the brand and its consumers, while also reflecting the values upheld by sunsilk. This study was conducted to determine the extent to which the brand ambassador influences the brand image of Sunsilk shampoo, using the VisCAP model, which consists of four dimensions: visibility, credibility, attractiveness, and power. The research employed a quantitative approach with an associative design. Data were collected through a survey distributed to 61 fourth-semester Communication Science students at Universitas Bina Sarana Informatika, Kalimalang Campus. Data were analyzed using simple linear regression and a t-test. The results show that the brand ambassador has a significant influence on brand image, with a t-value of 13.839 and a significance level of < 0.001. These findings indicate that selecting the right brand ambassador can positively contribute to shaping a strong brand image in the minds of consumers.